2011
DOI: 10.3390/mca16030617
|View full text |Cite
|
Sign up to set email alerts
|

The Approximate Solution of High-Order Linear Fractional Differential Equations with Variable Coefficients in Terms of Generalized Taylor Polynomials

Abstract: In this paper, we have developed a new method called Generalized Taylor collocation method (GTCM), which is based on the Taylor collocation method, to give approximate solution of linear fractional differential equations with variable coefficients. Using the collocation points, this method transforms fractional differential equation to a matrix equation which corresponds to a system of linear algebraic equations with unknown Generalized Taylor coefficients. Generally, the method is based on computing the Gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…Moreover, some numerical methods have been proposed for approximate solutions of this type equations such as the operational matrix method [10][11][12], Adomian decomposition method [13], homotopy-perturbation method [14], collocation method [15][16] and others [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some numerical methods have been proposed for approximate solutions of this type equations such as the operational matrix method [10][11][12], Adomian decomposition method [13], homotopy-perturbation method [14], collocation method [15][16] and others [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding to [13], the author's develop a new method called Generalized Taylor Collocation Method (GTCM) to give approximate solutions for linear fractional differential equations with variable coefficients. They found that this method is easy to write in computer codes and can be used as an effective method for obtaining analytic and approximate solutions for fractional differential equations.…”
Section: Numerical Solutions For Linear Fractional Differential Equatmentioning
confidence: 99%
“…Firstly, this method is based on taking the truncated Taylor series of the function in equations and then substituting their matrix forms in the given equation. Hence, the result of the matrix equation can be solved and the unknown Taylor coefficients can be found approximately [1,[3][4][5][6].…”
Section: Taylor Collocation Methodsmentioning
confidence: 99%